ANALISIS PENGARUH DANA PIHAK KETIGA, SERTIFIKAT BANK INDONESIA SYARIAH, BI RATE, DAN INFLASI TERHADAP PEMBIAYAAN MURABAHAH PERBANKAN SYARIAH DI INDONESIA PERIODE 2006-2014 - Budiyono, Iwan (Jurnal Sains Ekonomi dan Perbankan Syariah, 2015)
Abstract This research aims to analyze the influence of Third Party Funds, Bank Indonesia Islamic Certificate, BI rate, and inflation partially and simultaneously toward murabahah financing Islamic Banking in Indonesia 2006-2014 period. Population of this research is all of Islamic Banking in Indonesia 2006-2014 period. By using census sampling method obtained a sample all of Islamic Banking in Indonesia 2006-2014 period as samples. The data used in this study is secondary data. Data obtained from all of the financial statement Islamic Banking in Indonesia, which has averaged by Bank Indonesia and external data that contains BI rate and inflation on monthly 2006-2014 period. The analysis model uses multiple linear regression analysis models and analysis techniques to test the hypotesis uses, t test, F test, and R2 test. It is also tested the normality test and classical assumption by using SPSS 22.0 program.Result of testing hypothesis and discussion is Third Party Funds and inflation have positive and significant influence partially toward murabahah financing Islamic Banking in Indonesia 2006-2014 period. Meanwhile, Bank Indonesia Islamic Certificate and BI rate have negative and significant influence partially toward murabahah financing Islamic Banking in Indonesia 2006-2014 period as well as Third Party Funds, Bank Indonesia Islamic Certificate, BI rate, and inflation have influence simultaneously significant toward murabahah financing Islamic Banking in Indonesia. This research also found out that from four variables, while third party funds was the most dominant variable that influencing murabahah financing Islamic Banking in Indonesia 2006-2014 period.Keywords: Murabahah Financing, Third Party Funds, Bank Indonesia Islamic Certificate, BI Rate, Inflation.